USOS DOS ÍNDICES PET E UTCI NA AVALIAÇÃO DO CONFORTO TERMAL NO CAMPUS DA UFMT EM CUIABÁ-MT - Nince, Paulo Celso do Couto; Musis, Carlo Ralph de; Biudes, Marcelo Sacardi; Nogueira, José de Souza; Nogueira, Marta Crista de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707707 Existing procedures for evaluating the thermal environment in the areas weather, health,planning, tourism and recreation and climate research have significant deficiencies. Hoppe (1999)defined the index, physiological equivalent temperature (PET). The Commission of theInternational Society of Biometeorology developed the Universal Thermal Climate Index (UTCI).This paper investigates the variables temperature and humidity and indexes PET and UTCI toidentify the classes that are subject to thermal stress users of campus UFMT in different types ofcoatings soil and vegetation conditions of the microclimate in Cuiabá, Brazil. To this involvedmicrometeorological measurements at four points on campus for 43 continuous days during twoperiods: rainy and hot in a warm dry year 2012. The shadow of the hose during the day it wasfound: (i) the smaller Tbs Tbs as compared with those of the other points, (ii) the greatest relativehumidity, (iii) PET is much lower in two measurement periods, the other measuring points, (iv) theUTCI with index less than 35° C within the range of mild heat stress. Soon we see the importanceof providing shade in open spaces in tropical climates. As PET has exceeded the value of 50° C, inboth periods in critical hours therefore achieves the stress of extreme heat. The grass, concreteand asphalt during the day from 10 to 17h had rates up to 43° C, within the range of heat stressvery strong, but do not reach the age of extreme heat stress.